Manajemen Pembelajaran Pendidikan Agama Islam Berbasis Multikulturalisme Di SMK Al Khoiriyah Baron Nganjuk - Ahmad Masrukin; Mahfudh (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Multicultural education offers an alternative through the application of educational strategies and concepts based on the use of the diversity that exists in society, especially that of students, such as ethnic diversity, culture, language, religion, social status, gender, ability, age and race. SMK Al Khoiriyah is one of the multicultural schools, this can be seen from the diversity of cultural backgrounds possessed by students. This study uses a descriptive qualitative research approach. The implementation of multicultural-based Islamic religious education learning instils democratic values, solidarity and togetherness, compassion and forgiveness, peace and tolerance, in a way when the practice of worship by PAI teachers gives freedom to practice worship according to the flow they follow.